Analisis Persepsi dan Minat Mahasiswa Agribisnis untuk Melanjutkan Usahatani Keluarga (Kajian Pada Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang) - Fitra Razak, Moh Nabil; Abubakar, Abubakar; Nur'azkiya, Luthfi (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
This study aims to analyze the factors that influence the perceptions of agribusiness students and the factors that influence the interest of agribusiness students, as well as the relationship between the perceptions of agribusiness students and the interest of agribusiness students. This study uses primary data obtained from the results of questionnaire questions and secondary data. The sample used in this study consisted of 35 agribusiness students whose parents worked as rice farmers. The data analysis technique used is multiple linear regression test and Spearman test with the help of SPSS 24. The results showed that the factors that influenced the perceptions of agribusiness students were age, semester level, and cosmopolitan level. Then the factors that influence the interest of agribusiness students are land area, income, age, gender, and semester level. And there is a high correlation between the perceptions of agribusiness students and the interests of agribusiness students